Birds Without a Nest or The Refundación of The Peruvian Nation - Sáenz Leandro, Ronald (2020)
Aves sin nido (1889) by the Peruvian writer Clorinda Matto de Turner is a canonical work in the expression of the nineteenth century romantic narrative in the Americas. However, Matto's novel also stands out for the fact of presenting some aesthetic glimpses belonging to the realist-naturalist current, which leads to channel both aspirations for national construction and social criticism. The present work starts from the previous experts and postulates a reading in light of the possible confluences between elements such as race, class, sex, nation and political domination. This work concludes that the novel can be read as a proposal to refound the Peruvian nation from a perspective that privileges miscegenation, rural-urban migration and the bureaucratic modernization of the State. These elements are presented as the panacea that can free Peru from the historical-institutional legacies that prolong the backwardness and impede the renewal of values.